Flavonolignans As a Novel Class of Sodium Pump Inhibitors - Kubala, Martin; Čechová, Petra; Geletičová, Jaroslava; Biler, Michal; Štenclová, Tereza; Trouillas, Patrick; Biedermann, David (Frontiers in Physiology, 2016)
We examined the inhibitory effects of three flavonolignans and their dehydro- derivatives, taxifolin and quercetin on the activity of the Na+/K+-ATPase (NKA). The flavonolignans silychristin, dehydrosilychristin and dehydrosilydianin inhibited NKA with IC50 of 110 ± 40 μM, 38 ± 8 µM and 36 ± 14 µM, respectively. Using the methods of molecular modeling, we identified several possible binding sites for these species on NKA and proposed the possible mechanisms of inhibition. The binding to the extracellular- or cytoplasmic C-terminal sites can block the transport of cations through the plasma membrane, while the binding on the interface of cytoplasmic domains can inhibit the enzyme allosterically. Fluorescence spectroscopy experiments confirmed the interaction of these three species with the large cytoplasmic segment connecting transmembrane helices 4 and 5 (C45). The flavonolignans are distinct from the cardiac glycosides that are currently used in NKA treatment. Because their binding sites are different, the mechanism of inhibition is different as well as the range of active concentrations, one can expect that these new NKA inhibitors would exhibit also a different biomedical actions than cardiac glycosides.